How Strong Are Weak Patents? - Farrell, Joseph; Shapiro, Carl (American Economic Review, 2008)
We study the welfare economics of probabilistic patents that are licensed without a full determination of validity. We examine the social value of instead determining patent validity before licensing to downstream technology users, in terms of deadweight loss (ex post) and innovation incentives (ex ante). We relate the value of such pre-licensing review to the patent's strength, i.e., the probability it would hold up in court, and to the per-unit royalty at which it would be licensed. We then apply these results using a game-theoretic model of licensing to downstream oligopolists, in which we show that determining patent validity prior to licensing is socially beneficial. (JEL D82, K11, L24, O34)